2018
DOI: 10.1002/lom3.10291
|View full text |Cite
|
Sign up to set email alerts
|

Muddy waters: An assessment of the suitability of zygocardiac ossicles for direct age estimation in the Giant mud crab Scylla serrata

Abstract: A fundamental characteristic of calcified structures commonly used for direct age estimation in animals is that new material is accreted cumulatively and preserved across ontogeny, thus allowing growth marks to be reliably observed and counted. Direct age estimation in crustaceans has been problematic due to molting of calcified structures across ontogeny; however, recent studies suggest that gastric ossicle tissue is retained through molts and can be used for age estimation. We evaluate the use of sectioned g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Annual band deposition, however, defies current understanding of ecdysis and hard structure reformation (Vatcher et al, 2015;Becker et al, 2018, Crook et al, 2018Sheridan & O'Connor, 2018). These recent studies showed that gastric ossicles were completely moulted, which challenges the proposed direct relationship between cuticle bands and chronological age (Vatcher et al, 2015;Sheridan et al, 2016a, b;Becker et al, 2018;Crook et al, 2018).…”
Section: Calcein Stainingmentioning
confidence: 96%
“…Annual band deposition, however, defies current understanding of ecdysis and hard structure reformation (Vatcher et al, 2015;Becker et al, 2018, Crook et al, 2018Sheridan & O'Connor, 2018). These recent studies showed that gastric ossicles were completely moulted, which challenges the proposed direct relationship between cuticle bands and chronological age (Vatcher et al, 2015;Sheridan et al, 2016a, b;Becker et al, 2018;Crook et al, 2018).…”
Section: Calcein Stainingmentioning
confidence: 96%
“…Previous studies have demonstrated that these ossicles contain rings or layers of calcified growth features, much like fish otoliths, which could potentially be used as a method of direct ageing (Kilada et al ., 2012; Leland & Bucher, 2017). More recently, chemical staining and rearing studies have provided additional support that the ‘ring-like’ structures observed within these ossicles may contain chronological information (Kilada et al ., 2015; Leland & Bucher, 2017), however there continues to be a debate as to whether or not the gastric mill is actually retained through the moulting process (Vatcher et al ., 2015; Sheridan et al ., 2016; Becker et al ., 2018; Crook et al ., 2018). Gastric mill growth features have been observed in an increasing number of species (Kilada & Acuña, 2015; Kilada et al ., 2015; Kilada & Driscoll, 2017), but few long-term studies have been conducted to confirm the temporal periodicity of these marks.…”
Section: Introductionmentioning
confidence: 99%